The Influence of Compensation on Employee Performance Through Commitment and Motivation at PT. Bank Rakyat Indonesia (Persero) Tbk. Abunjani Sipin Branch, Jambi - Trismi A, Linda; Zahari, M; Hapsara, Osrita (International Journal of Advanced Multidisciplinary, 2025)
This research aims to achieve several objectives, which include: 1) Explaining the aspects of compensation, commitment, motivation, and employee performance at Bank BRI Abunjani Sipin Jambi Branch; 2) Examining the influence of compensation on employee commitment; 3) Investigating the impact of compensation on employee motivation; 4) Assessing the effect of compensation on employee performance; 5) Evaluating how commitment affects employee performance; 6) Analyzing the influence of work motivation on employee performance; 7) Studying the effect of compensation on employee performance mediated by commitment; and 8) Assessing the effect of compensation on employee performance mediated by motivation. The study's population comprises 114 employees at the BRI Sipin Branch in Jambi City in 2023, with a saturated sampling technique being utilized. This research employs a quantitative methodology with a survey approach and utilizes Partial Least Squares (PLS) for data analysis. The findings reveal that compensation exerts both direct and indirect positive and significant effects on employee performance, mediated by commitment and motivation. Furthermore, commitment and motivation themselves have a direct and significant positive influence on employee performance. These findings indicate that when the compensation provided aligns with employees xpectations, it enhances their commitment and motivation, resulting in improved work performance.